Analytical study of functional outcome of extracapsular proximal femur fracture fixation by cephalomedullary nail system - R. Ramaraj; P. Balasubramaniyan; Umasanker (Journal of Orthopaedic Reports)
Background: Intertrochanteric(IT) fracture is one of the most common fractures in adult population. Cephalo medullary nailing is a common surgical treatment for trochanter fracture. We studied trochanter fractures of the grown-ups in age group- 40 years and over(both gender). Displaced extracapsular fractures of the upper femur who presented to the ortho out patient or casualty were added for the study. Cases were reassessed in the ward for neurovascular injuries and any other associated injuries. Surgery was planned after getting written informed consent.Patients were posted after anaesthetic fitness. All cases were followed up regularly clinically And radiologically for fracture union and other complications if any. Aim: TO STUDY FUNCTIONAL result OF EXTRACAPSULAR PROXIMAL FEMUR FRACTURE FIXATION BY CEPHALOMEDULLARY NAIL SYSTEM. Results: 43 patients in the age group above 40 were studied. all the patients got united fracture. few complications of malunion and screw backout noted. overall good results obtained. Conclusion: The use of a cephalomedullary system for extracapsular femur fracture is associated with a high rate of successful fracture healing and restoration of function, allowing patients to return to their pre-injury position of exertion.